2
$\begingroup$

If $z_1 = r_1(\cos\theta_1+i\sin\theta_1)$ and $z_2 = r_2(\cos\theta_2+i\sin\theta_2)$ prove that $\left|\frac{z_1}{z_2}\right|=\frac{|z_1|}{|z_2|}$ and that $\arg\left(\frac{z_1}{z_2}\right)=\arg z_1-\arg z_2$.

I've done most of this, but I got stuck at the end:

$$\begin{align} \frac{z_1}{z_2}&=\frac{r_1(\cos\theta_1+i\sin\theta_1)}{r_2(\cos\theta_2+i\sin\theta_2)}\\ &=\frac{r_1}{r_2}\cdot\frac{(\cos\theta_1+i\sin\theta_1)(\cos\theta_2-i\sin\theta_2)}{1}\\ &=\frac{r_1}{r_2}\cdot[(\cos\theta_1\cos\theta_2+\sin\theta_1\sin\theta_2)+i(\sin\theta_1\cos\theta_2-\cos\theta_1\sin\theta_2)]\\ &=\frac{r_1}{r_2}\cdot[\cos(\theta_1-\theta_2)+i\sin(\theta_1-\theta_2)]\\ \\ \left|\frac{z_1}{z_2}\right|&=\sqrt{\frac{r_1^2}{r_2^2}\cdot[\cos(\theta_1-\theta_2)+i\sin(\theta_1-\theta_2)]^2} \end{align}$$ But in order for this to work, $[\cos(\theta_1-\theta_2)+i\sin(\theta_1-\theta_2)]^2$ must equal $1$ (so that $\left|\frac{z_1}{z_2}\right|=\frac{r_1}{r_2}$), but it doesn't. Where am I going wrong?

$\endgroup$
  • $\begingroup$ Do you know that $|z_1z_2|=|z_1|\,|z_2|$ and that $\arg(z_1z_2)=\arg z_1+\arg z_2$? $\endgroup$ – egreg Nov 2 '14 at 16:01
  • $\begingroup$ Where did that square root come from? Can't you use that |z| = r when z = r(cosθ+isinθ)? $\endgroup$ – ypercubeᵀᴹ Nov 2 '14 at 16:02
  • $\begingroup$ @egreg When I look at the proof for that statement, it also ends up in the same situation: $|z_1 z_2|=\sqrt{r_1^2 r_2^2 [\cos(\theta_1+\theta_2+i\sin(\theta_1+\theta_2)]^2}=r_1 r_2$ $\endgroup$ – hohner Nov 2 '14 at 16:03
7
$\begingroup$

The step you take to the last equation isn't right; recall that the absolute value of a complex number is defined as $$|a+bi|=\sqrt{a^2+b^2}$$ but you've just written it as $$|z|=\sqrt{z^2}$$ which only works for real $z$. If you use the proper (first) identity, noting that the second to lasts equation is easy to separate into imaginary and real parts, you will get to $$\left|\frac{z_1}{z_2}\right|=\sqrt{\frac{r_1^2}{r_2^2}\cdot[\cos(\theta_1-\theta_2)^2+\sin(\theta_1-\theta_2)^2]}$$ which will work out as you expect.

$\endgroup$
  • $\begingroup$ Ahh, I understand now. Thank you :) $\endgroup$ – hohner Nov 2 '14 at 16:07
0
$\begingroup$

If $z_1=r_1(\cos\theta_1+i\sin\theta_1)$ and $z_2=r_2(\cos\theta_2+i\sin\theta_2)$ it's just a matter of computations with the addition formulas to show that $$ z_1z_2=r_1r_2(\cos(\theta_1+\theta_2)+i\sin(\theta_1+\theta_2)) $$ so $$ |z_1z_2|=r_1r_2=|z_1|\,|z_2|,\qquad \arg(z_1z_2)=\theta_1+\theta_2=\arg z_1+\arg z_2 $$ For the quotient, set $w_1=z_1/z_2$ and $w_2=z_2$; then $$ |w_1w_2|=|w_1|\,|w_2| $$ or $$ |z_1|=\left|\frac{z_1}{z_2}\right|\,|z_2| $$ For the arguments it's the same.

In order to show that $|z_1z_2|=|z_1|\,|z_2|$ you can also prove first that $$ \overline{z_1z_2}=\overline{z_1}\,\overline{z_2} $$ which is just computations (use $z_1=a_1+ib_1$, $z_2=a_2+ib_2$). Then $$ |z_1z_2|^2=z_1z_2\cdot\overline{z_1z_2}= z_1z_2\overline{z_1}\overline{z_2}= z_1\overline{z_1}z_2\overline{z_2}= |z_1|^2|z_2|^2 $$ and the conclusion follows by taking square roots.

$\endgroup$
0
$\begingroup$

Well $\frac{z_1}{z_2}=\frac{r_1}{r_2}e^{i(\theta_1-\theta_2)}$. And $|e^{i(\theta_1-\theta_2)}|=1$ So $|\frac{z_1}{z_2}|=\frac{r_1}{r_2}=\frac{|z_1|}{|z_2|}$ . all is used is Pythagorean's to get $|\frac{r_1}{r_2}e^{i(\theta_1-\theta_2)}|=1$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.